Environmental Disasters and Socio-Spatial Conflicts in Brazil - da Mata Siqueira, Antenora Maria; Nazareno Mendes, Juliana; Lemos Filho, Alex José (Geografares, 2017)
Water-related disasters occurred in Brazil deepened and expanded researches on such phenomena. This article analyzes the conflicts arising from the response of the government of the city of Campos dos Goytacazes / RJ concerning the consequences of these disasters: the public housing program "Morar Feliz". There were conducted bibliographic researches, data collection in public entities and interviews with residents resettled. The results indicate the existence of conflict of interests that opposes residents who claim to stay in the district in which they reside, or close to it; and the municipal government, which promotes urban sprawl in areas with lack of urban infrastructure. Keywords: Environmental disasters, public housing, risk.